Integrated Wi-Fi Sensing and Communication for Soil Moisture Monitoring - Silva, Henrique Freire da; Albertini, Bruno de Carvalho; Margi, Cíntia Borges (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2026)
Soil moisture monitoring is essential for efficient irrigation and crop management in precision agriculture. Conventional methods rely on manual sampling or dedicated sensors, which limit large-scale deployment due to cost and infrastructure requirements. RF-based sensing offers an alternative by exploiting changes in signal amplitude and phase caused by soil dielectric properties. This work evaluates soil moisture sensing using Wi-Fi on resource-constrained ESP32 devices in a laboratory and an in the field. Our study takes into consideration the distance between devices, and the CSI amplitude and phase. Confined experiments introduced bias in channel metrics, while field tests revealed sensing limitations with increasing range.